DYNAMIC OF QUALITY MANAGEMENT IN HIGHER EDUCATION : A SYSTEMATIC ANALYSIS OF KEY DETERMINANTS - Ian, Rinovian Rais; Al Ghazali; Chandra Sagul Haratua (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Quality management in higher education has shifted from merely meeting administrative standards to becoming a strategic instrument for maintaining global competitiveness. This article aims to systematically analyze the key determinants influencing the dynamics of quality management implementation in higher education institutions. Through a systematic literature review of 30 selected references, this study maps four crucial determinants: visionary leadership and organizational culture, information technology integration, faculty competence and engagement, and external regulatory pressures. The analysis shows that successful quality assurance cannot be achieved in isolation but requires a harmonious orchestration of managerial aspects, digital infrastructure readiness, and human resource commitment. This article provides a new theoretical contribution by viewing quality management as a dynamic and adaptive ecosystem to changing times. Keywords: Quality Management, Higher Education, Leadership, Technology Integration, Organizational Culture